Evidence-Based Clinical Social Work: Subject Matter and Perspectives - Deimel, Daniel (Gesundheitswesen (Bundesverband der Ärzte des Öffentlichen Gesundheitsdienstes (Germany)), 2019)
Clinical social work has established itself as a health-specific profession in Germany over the past 15 years. It refers to a bio-psycho-social health understanding and is particularly focused on hard-to-reach client groups. The concept of evidence-based practice is often criticized and rejected by parts of the profession and discipline of social work. The concepts of evidence-based medicine and clinical social work are associated with positive outcomes for clinical practice and professional development.